Rendimento discente no ENADE e seu detalhamento nos conteúdos específicos dos cursos de Ciências Contábeis do Brasil - Martins, Nicolle Caroline Brasil (2019)
he economic, social, as well as current political scenario has demanded Accounting professionals who, in their training process, add technical and professional qualification, as well as ethics in relation to the conduct and the exercise of the accounting profession VIANNA,2000; MIRANDA, 2011; FERREIRA et al., 2015). This scenario demonstrates the context in which Accounting teaching is inserted in Brazil marked by the expansion of higher education, as well as in an expansion in the offer of the strictosensu postgraduate programs of the Accounting Sciences courses, in addition to the constant modifications throughout the wrapped in national and international accounting (MIRANDA, 2011). It can be understood that the union of these events can influence the process of professional formation and, consequently, the student academic performance as a whole, thus motivating researches that seek to analyze the quality of the education offered. The performance of the students of the courses of Accounting Sciences of Brazil has been shown low, according to reports published by INEP, the average of the ENADE concept for questions of specific content is of 34.4. From these indications, the general objective of this study was to investigate student performance by specific content of professional training in the National Student Performance Examination - ENADE in the year 2015 and the characteristics of the Brazilian Accounting Sciences courses. The Theory of Educational Production Function was the theoretical basis adopted in the study. A sample of 53,995 students from the accounting sciences courses who completed ENADE in 2015 was selected (82.57 % of the population). Initially, the classification no feach issue of the ENADE of 2015 and organization of areas of specific content was carried out based on INEP's 439 ordinance for subsequent descriptive statistical analysis of the issues. Soon after, the Theory of Response to the ITEM - TRI was used to measure the students' abilities to answer the questions of the EXAM. From this, the nonparametric Kruskal-Wallis test was used to observe the effect of the factors Region, Administrative Organization, Teaching Modality and Administrative Category on students' performance by specific content. As findings it is presented that the students obtained better performance in the issues of Controllership and Management Accounting. The Southeast and Northeast regions presented better performance in the detailing of the specific content, as well as the students of public institutions of face-to-face teaching. It should also be noted that at the level of Administrative Organization some warnings for Universities and Colleges that presented inferior performance to the Federal Institutes and University Centers, respectively, in relation to all specific contents. As a main contribution of these findings, it should be pointed out that this study proposes warnings to HEIs, as well as to coordinations and other bodies for the promotion of higher education in Accounting Sciences, regarding contents that present greater weaknesses in relation to academic performance, motivating the improvement of teaching faster and more targeted.